Thermally-activated stress relaxation in a model amorphous solid and the formation of a system-spanning shear event. (15th January 2018) - Derlet, P.M.; Maaß, R.
Abstract: Molecular dynamics simulations are performed to investigate the underlying thermally activated processes contributing to stress relaxation in a model binary amorphous system. Amorphous samples are first shear strained at zero kelvin and then the temperature is ramped up to the glass transition regime. Four orders of magnitude in the temperature ramp rate are considered. It is found that depending on the degree to which the amorphous solid is relaxed, significant atomic-scale scale activity is seen well below the glass transition regime, and that this is largely independent of the external load. The stress relaxation below the glass-transition temperature is mediated by spatially localized and thermally activated structural excitations. Over time, such thermally driven stochastic activity can collectively lead to a global gauge shearing, the location of which correlates with regions of low icosahedral content with lower coordination and higher density. Graphical abstract: Image 1